ANALYSIS OF THE FINANCIAL MANAGEMENT AND LITERATION INFLUENCE ON THE FAMILY WELFARE LEVEL (CASE STUDY ON MUSLIMAH WITH TEACHER'S PROFESSION IN SELONG DISTRICT) - Diah Zikrina Mulyarti; Yaser Taufik Syamlan (Jurnal Internasional Ekonomi Islam, 2019)
The purpose of this research is to determine wether the financial management variable and financial literacy affect family welfare of muslimah teachers at Selong. 221 repondents were used as the sample in this research. the answers of those respondents were submitted using questionnaire with multinominal logistic regression as the method used to process the data. this research use two independent variable which is financial management variable and financial literacy variable and one dependent variable which is family welfare. the result of this research stated that financial management variable (X1) affect family welfare of muslimah teacher at Selong sub-district while financial literacy variable (X2) wasn’t.